PENYUSUNAN ZONASI TAMAN NASIONAL MANUPEU TANADARU, SUMBA BERDASARKAN KERENTANAN KAWASAN DAN AKTIFITAS MASYARAKAT (Zoning System Development of Manupeu Tanadaru National Park on Sumba based on Area Sensitivity and Community Activities) - Syarif Indra S.P; Lilik Budi Prasetyo; Rinekso Soekmadi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Manupeu Tanadaru forest block was designated as National Park based on Ministry of Forestry and Plantation Decree No.576/Kpts-II/1998. The designation has not been followed by boundary demarcation and a proper management plan. There is a different perception between government and community on the existence of the national park that has led to a conflict between forest protection and biodiversity conservation with community livelihood. The objective of this research is to develop zoning system of Manupeu Tanadaru National Park based on area sensitivity and community activities. Area sensitivity was defined based on biological and physical condition analysis, consists of erosion area analysis, water catchments area analysis and wildlife protection area analysis. Community activities was defined based on type and distribution of local community activities inside the national park. Result of this research show that about 52.89% of the national park was area with high to very high sensitivity level that should be allocated as “Wilderness Zone and Core Zone”. About 12.36% of the national park is used by local community for agriculture, non timber forest product, sacred place and water resource for subsistence needs in area with low to middle sensitivity level that should be allocated as “Traditional Zone and Other Use Zone”.Key words: national park, area sensitivity, community activities, zoning system